English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-03-03 03:37:17 · 8 answers · asked by rippedtroll 2 in Science & Mathematics Mathematics

8 answers

Case i
n is odd
=>n^2 is odd
=>n^2 + n is even ( odd num + odd num is even )
Case ii
Follow same principles.

Or even better
n^2 + n = n(n+1)
=>It is the product of two consecutive numbers
=>At least one is an even number
=>Product is even

2007-03-03 03:43:01 · answer #1 · answered by FedUp 3 · 2 0

let n=3
therefore n^2+n=3^2+3
=9+3
=12
let n=4
therefore n^2+n=4^2+4
=16+4
=20
hence every natural number n is even for the above case

2007-03-03 03:46:35 · answer #2 · answered by bksrikanth 1 · 0 0

If you are want to prove it using mathematical induction:

Prove statement true for n:=1
(1)^2+1:=2
Statement is true for n:=1

Assume statement true for n:=k
i.e (k)^2+k gives an even number

Prove statement true for n:=k+1
i.e (k+1)^2+k+1

(k+1)^2+K+1=k^2+2k+1+K+1
=((k)^2+k)+2k+2

Statement is true as the result will give an even number.

By the principle of mathematical induction the statement is true for every natural number n.

2007-03-03 04:15:52 · answer #3 · answered by Y001 2 · 0 0

First factor it to get n(n+1)

n and n+1 are consecutive numbers so one will be even and one odd

The product of an even and odd number is always even

2007-03-03 03:44:12 · answer #4 · answered by hayharbr 7 · 0 0

Simple: if n is odd, then n + 1 is even, so their product

n(n + 1) = n^2 + n

is even. Similarly, if n is even, then n^2 + n is again the product of an odd and an even number, and so is even.

2007-03-03 03:45:29 · answer #5 · answered by MHW 5 · 1 0

n^2+n=n(n+1) is the procut of two consecutive numbers so one is even and so the product

2007-03-03 03:44:16 · answer #6 · answered by santmann2002 7 · 0 0

n^2 + n = n(n + 1) so that if n is even then (n + 1 is odd and the product od odd and even = even

If n is odd then (n + 1) is even ans again the product of even and odd = even

2007-03-03 03:45:22 · answer #7 · answered by physicist 4 · 0 0

a)P(a million) - 3*a million/= ok^2+6>3k+3 for this reason ok^2+4+2k >3k+3

2016-11-27 02:00:01 · answer #8 · answered by ? 4 · 0 0

fedest.com, questions and answers